2020 Otto Aufranc Award: Malseating of modular dual mobility liners: incidence and implications. (July 2020) - Romero, Joey; Wach, Amanda; Silberberg, Scott; Chiu, Yu-Fen; Westrich, Geoffrey; Wright, Timothy M.; Padgett, Douglas E.
Abstract : Aims: This combined clinical and in vitro study aimed to determine the incidence of liner malseating in modular dual mobility (MDM) constructs in primary total hip arthroplasties (THAs) from a large volume arthroplasty centre, and determine whether malseating increases the potential for fretting and corrosion at the modular metal interface in malseated MDM constructs using a simulated corrosion chamber. Methods: For the clinical arm of the study, observers independently reviewed postoperative radiographs of 551 primary THAs using MDM constructs from a single manufacturer over a three-year period, to identify the incidence of MDM liner-shell malseating. Multivariable logistic regression analysis was performed to identify risk factors including age, sex, body mass index (BMI), cup design, cup size, and the MDM case volume of the surgeon. For the in vitro arm, six pristine MDM implants with cobalt-chrome liners were tested in a simulated corrosion chamber. Three were well-seated and three were malseated with 6° of canting. The liner-shell couples underwent cyclic loading of increasing magnitudes. Fretting current was measured throughout testing and the onset of fretting load was determined by analyzing the increase in average current. Results: The radiological review identified that 32 of 551 MDM liners (5.8%) were malseated. Malseating was noted in all of the three different cup designs. The incidence of malseating was significantly higher in low-volume MDM surgeons than high-volume MDM surgeons (p < 0.001). Pristine well-seated liners showed significantly lower fretting current values at all peak loads greater than 800 N (p < 0.044). Malseated liner-shell couples had lower fretting onset loads at 2, 400 N. Conclusion: MDM malseating remains an issue that can occur in at least one in 20 patients at a high-volume arthroplasty centre. The onset of fretting and increased fretting current throughout loading cycles suggests susceptibility to corrosion when this occurs. These results support the hypothesis that malseated liners may be at risk for fretting corrosion. Clinicians should be aware of this phenomenon. Cite this article: Bone Joint J 2020;102-B(7 Supple B):20–26.